2023
DOI: 10.1021/acs.jafc.2c08679
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors ZjMYB39 and ZjMYB4 Regulate Farnesyl Diphosphate Synthase- and Squalene Synthase-Mediated Triterpenoid Biosynthesis in Jujube

Abstract: Jujube (Ziziphus jujuba Mill.) is rich in valuable bioactive triterpenoids. However, the regulatory mechanism underlying triterpenoid biosynthesis in jujube remains poorly studied. Here, we characterized the triterpenoid content in wild jujube and cultivated jujube. The triterpenoid content was higher in wild jujube than in cultivated jujube, triterpenoids were most abundant in young leaves, buds, and later stages of development. The transcriptome analysis and correlation analysis showed that differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although the role of squalene as an ergosterol precursor is well known ( 22 ), recent papers have shown that alternative functions of SqsA and SqsA-like enzymes and subsequent squalene synthesis are involved in induction of terpenoids in plants ( 23 , 24 ) and bacteria ( 25 ). We thus hypothesized that A. nidulans transformants expressing PdFAC1 could be altered in terpenoid production.…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of squalene as an ergosterol precursor is well known ( 22 ), recent papers have shown that alternative functions of SqsA and SqsA-like enzymes and subsequent squalene synthesis are involved in induction of terpenoids in plants ( 23 , 24 ) and bacteria ( 25 ). We thus hypothesized that A. nidulans transformants expressing PdFAC1 could be altered in terpenoid production.…”
Section: Resultsmentioning
confidence: 99%
“…Geranylgeranyl diphosphate (GGPP) produced by GGDS serves as a precursor for many diphosphates, including farnesyl-PP, Geranylgeranyl-PP, and Geranyl-PP [ 52 , 53 ]. Farnesyl-diphosphate (FPS) reduced farnesyl-PP to squalene, and then squalene monooxygenase (SME) oxidized squalene to (s)-squalene-2, 3-epoxide in sesquiterpenoid and triterpenoid biosynthesis [ 54 , 55 ]. Up-regulation of FPS and SME transcripts may indicate a relatively high accumulation of F-PP and squalene for sesquiterpenes and monoterpenes in HW.…”
Section: Discussionmentioning
confidence: 99%
“…Wen (2023) [63] further explored the role of ZjWRKY18 (evm.model.Contig24.0.57) in activating ZjHMGR (evm.model.Contig21.0.64 and evm.model.Contig112.45) and ZjFPS, promoting triterpene accumulation. Wen et al (2023) [64] analyzed enzymes related to terpenoid synthesis through transcriptome analysis and identified ZjFPS, ZjSQS, and the corresponding transcription factors, ZjMYB39 (evm.model.Contig108.375) and ZjMYB4 (evm.model.Contig23.4.315), as key genes for the biosynthesis of jujube triterpenoids. However, the corresponding transcription factor of ZjSQE is still unclear (Figure 2).…”
Section: Terpenoid Biosynthesismentioning
confidence: 99%